Era Cyberspace Sebagai Prospek dan Tantangan Pendidikan Karakter Bangsa - Tri Karyono (Universitas PGRI Adi Buana Surabaya, 2019)
Cyberspace era is characterized by the blurring the different types of boundaries including nations, and is signalized by leaving the data trace (log files) and not leaving the physical documents (paperless). Industrial revolution 4.0 with its use of cyber physical systems is no exception. Information technology at one pointmakes the distance closer, but at another point it potentially also leads to educational, social, cultural and behavioural problems. In this regards, there should be an awareness of how to create healthier environment. This study, therefore, is aimed at providing illustrative solutions of the problems in connection with the accessibility of diverse information in the era of cyberspace which affect on the people’s way of thinking, actions and attitudes. The results of this study are expected to contribute to the ideas of charater education which is being the core to achieve the quality of national education in Indonesia. Moreover, the results of the study are expected to provide some insights of how to help society smarter in the era of cyberspace in which eventually they will have a capacity to reduce the big data information and empower this information for their better life.